Evaluation of annealed titanium oxide nanotubes on titanium: From surface characterization to in vivo assays - Gomez Sanchez, Andrea Valeria (2020)
The entire route from anodic oxidation and surface characterization, including in vitro experiments and finally in vivo osseointegration assays were performed with the aim to evaluate nanotubular and crystalline annealed titanium oxides as a suitable surface for grade 2 titanium permanent implants. Polished titanium (T0) was compared with anodized surfaces obtained in acidic media with fluoride, leading to an ordered nanotubular structure of titanium oxide on the metal surface, characterized by tube diameter of 89 ± 24 nm (Tnts). Samples were thermally treated in air (TntsTT) to increase the anatase crystalline phase on nanotubes, with minor alteration of the structure. Corrosion tests were performed to evaluate the electrochemical response after 1, 14, and 28 days of immersion in simulated body fluid. Based on the in vitro results, heat-treated titanium nanotubes (TntsTT) were selected as a promissory candidate to continue with the osseointegration in vivo assays. The in vivo results showed no major improvement in the osseointegration process when compared with untreated Ti after 30 days of implantation and there also was a lower increase in the development of new osseous tissue.